Dimeric BODIPY-loaded liposomes for dual hypoxia marker imaging and activatable photodynamic therapy against tumors. Issue 26 (21st June 2018) - Chen, Huachao; Bi, Qirui; Yao, Yongrong; Tan, Ninghua
Abstract : This work reports a dimeric BODIPY (BDP)-loaded liposome with conjugation of anti-HIF antibodies for dual hypoxia marker imaging and nitroreductase (NTR)-activatable photodynamic therapy (PDT) against hypoxic tumors. Abstract : This work reports a dimeric BODIPY (BDP)-loaded liposome with conjugation of anti-HIF antibodies for dual hypoxia marker imaging and nitroreductase (NTR)-activatable photodynamic therapy (PDT) against hypoxic tumors. In this theranostic nanosystem (designated Ab-DiBDP NPs), the newly designed orthogonal BDP dimer has high 1 O2 quantum yield, and the substitution of a nitro group at the meso -position leads to the NTR-controllable activation of phototoxicity and fluorescence. Both in vivo and in vitro experiments demonstrate that the NTR-activatable PDT liposome can efficiently destroy cancer cells and prevent damage to normal cells. More significantly, the fascinating advantage of the nanoprobe is the synergy between the Cy 7-marked anti-HIF-1α antibody and the NTR-activatable DiBDP, which significantly improves the accuracy of tumor hypoxia imaging by simultaneous detection of NTR and HIF-1α. Therefore, this work presents a new paradigm for NTR-triggered PDT against cancer cells and provides a new avenue for precise tumor hypoxia diagnosis.